A multi‐system geochronology in the Ad‐3 borehole, Pannonian Basin (Hungary) with implications for dating volcanic rocks by low‐temperature thermochronology and for interpretation of (U–Th)/He data. (29th May 2015) - Danišík, Martin; Fodor, László; Dunkl, István; Gerdes, Axel; Csizmeg, János; Hámor‐Vidó, Mária; Evans, Noreen J.
Abstract Independent geochronological and thermal modelling approaches are applied to a biostratigraphically exceptionally well‐controlled borehole, Alcsútdoboz‐3 (Ad‐3), in order to constrain the age of Cenozoic geodynamic events in the western Pannonian Basin and to test the efficacy of the methods for dating volcanic rocks. Apatite fission track and zircon U–Pb data show two volcanic phases of Middle Eocene (43.4–39.0 Ma) and Early Oligocene (32.72 ± 0.15 Ma) age respectively. Apatite (U–Th)/He ages (23.8–14.8 Ma) and independent thermal and subsidence history models reveal a brief period of heating to 55–70 °C at ~17 Ma caused by an increased heat‐flow related to crustal thinning and mantle upwelling. Our results demonstrate that, contrary to common perception, the apatite (U–Th)/He method is likely to record 'apparent' or 'mixed' ages resulting from subsequent thermal events rather than 'cooling' or 'eruption' ages directly related to distinct geological events. It follows that a direct conversion of 'apparent' or 'mixed' (U‐Th)/He ages into cooling, exhumation or erosion rates is incorrect.